SELF-MANAGEMENT AS A MEANS OF PROFESSIONAL PERSONALITY DEVELOPMENT OF FUTURE TEACHERS - N.Yu. Dudnik (Academy of Cognitive and Natural Sciences, 2022)
In this article is spoken about necessity of formation of  students skills to self-management fo r their professional development in the pedagogical sphere.